(3QSGdI aj GdWHs - (3GdCMfa Hf bjUQs
(3ChdgG (B:s
(3bGd GdCMfa Hf bjUQ ENJGQ GdMceGA ef cdGe GdMceI CQHYI BdGa cdeI Ke ENJGQhG CQHY cdeGJ GdChd dGJKbf HGdfSGA GdKGfjI dGJMed eYOJc eGdG JWjbg GdKGdKI dGjZQfc GdeGd hEf cKQ GdQGHY jcajc ef GdYde eG jfJaY s
(3BNQgG (B:s
(3hgj GdJi JZjH jhejf hJfhH jhekG dG JcGO dfbWY aMjfFP jfJai Cf jTQ eSgd GdThGA hfPcQg ai GdHGH GdKGfi eY GdGOhjI EfTGA Gddg JYGdi gPg GdePchQGJ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B6s
(3HgG fXGe GdJYbjHIs
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdCSJGP (B- (3YHO GdeMSf Hf MeO GdYHGO s
Keywords: (3GdWHs